(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Climate change have wide-ranging effects on the environment, and socioeconomic further which may include the water resources, agriculture and food security, human health, terrestrial ecosystems and biodiversity and coastal zones. Some impacts will gradually affect economic processes, such as the effect of increasing temperature on energy demand, whereas others may come as extreme events, such as sudden floods or forest fires. The depletion of natural resources, as a result of increased environmental and demographic pressures, tends to aggravate the severity of climate change impacts. All in all, there are increasing concerns about the rising threats to current income and consumption patterns of households and individuals that earn their livelihoods from these sectors (Foresight, 2011; IPCC, 2012). Methods: The research design of the present study was descriptive in nature. Two sampling techniques namely purposive & random sampling were used for the selection of the respondents in the present study. First of all a zone wise list of Vadodara city was collected from the Health Department of Vadodara Municipal Corporation (VMC) for the mapping of the Vadodara city than the list was divided into 4 different zones with 34 areas with the help of purposive sampling method. The samples size of 10000 were selected randomly (divided equally within four different zones of the city) from each selected areas and the responses were collected from the family member who was ready to give response. For collection of data interview schedule along with observation and discussion were used as a main tool. For analyse of data simple percentages was used. Findings: From the study it was found that there is a variation in terms of problems faced by the respondents in different zones. It is observed that majority (95%) of the respondents stated that their energy consumption (in terms of electricity, petrol/Diesel, LPG/Kerosene) is increasing year by year due to climatic changes. The study reveals that majority of the respondents are facing difficulties for going to work during floods and facing difficulties in managing their daily supply of grocery and also some medical treatments. It is observed that the water logging problem is associated with lack of proper roads, sewerage and drainage system and the areas are situated in below the road line. The study reveals that the rain and flood is affecting the respondents in terms of various kinds of losses which includes the loss of assets, stored grains, children’s textbooks, shoes, bags, & electronic devices etc. Wall, door, roof and windows of the houses are also not safe. Some people haven’t registered their damages occurred by flood in terms of amount. From the study it was found that in all the zones the major cost was associated with wastage of flood items, repairing charges of vehicle/assets/electrical items, damage of wall etc. The study also shows that 50.38 percent of the respondents from West Zone, 42.70 percent from North and South Zone and 41.67 percent from East Zone. Mentioned that they are managing their extra health related expenses out of their savings. The study also reveals that some of the respondents didn’t have any provision in their budget to take medical services and due to this they sold their property or assets in order to bear the expenses for treatment of diseases. On the basis of data it was also found that the rate of purchasing of AC & cooler is also increased year-by-year. Conclusion: On the basis of the study it can be concluded that the climate change is affecting the people of Vadodara in various ways. The socio-economic impacts of the climate is vary from zone to zone due to the sewerage issues, socio-economic condition, and sea level of the area along with geography location of the area. Loss of property, assets, food grains, damage of houses due to flood are the major reasons of economic loss and which is going to affect their quality of life also.